Advanced bioH2 and bioCH4 production with cobalt-doped magnetic carbon. Issue 68 (17th November 2020) - Zhang, Jishi; Zhao, Wenqian; Fan, Chuanfang; Li, Wenqing; Zang, Lihua
Abstract : In this work, a novel cobalt-doped magnetic carbon (CDMC) was prepared to boost hydrogen (H2 ) and methane (CH4 ) generation. Abstract : In this work, a novel cobalt-doped magnetic carbon (CDMC) was prepared to boost hydrogen (H2 ) and methane (CH4 ) generation. A one-pot approach was employed to produce H2 and CH4 with an incompletely heat-treated mixed culture. A moderate amount of CDMC promoted biogas evolution, while excess CDMC eroded both H2 and CH4 productivity. The CDMC (600 mg L −1 ) group achieved the highest biogas yields of 176 mL H2 per g glucose and 358 mL CH4 per g glucose, which were higher than those (102 mL H2 per g glucose and 288 mL CH4 per g glucose) found in the control group without CDMC. The mechanisms of H2 and CH4 production via the one-pot approach with CDMC were speculated to be as follows: CDMC provided beneficial sites and two elements (Co and Fe) for culture growth and boosted electron transfer, facilitating glucose degradation and conversion. Supplementation of carbon matrix composites and trace elements in biogas production has been shown to be an efficient strategy.